Reformulation of Cybercrime Regulations in The Misuse of Artificial Intelligence in Indonesia - Dosni Ana Ragita Pakpahan; Anis Widyawati (Universitas Negeri Semarang, 2026)
The rapid development of AI has increased the potential for cybercrime through increasingly sophisticated, automated, and wide-scale abuse methods. In Indonesia, the regulation of cybercrimes related to the abuse of AI is still fragmented and generally relies on general provisions on cybercrimes, so it does not fully accommodate the specific characteristics and risks of AI technology. This study aims to analyze the regulation of cybercrime in the abuse of AI in Indonesia, examine the regulatory approach applied in the European Union, and formulate a reformulation of cybercrime regulations in the misuse of artificial intelligence in Indonesia. This study uses a normative legal research method with a statute approach and a comparative approach conducted through literature studies. Primary legal materials include Indonesian and European Union laws and regulations, as well as other regulations, which are supported by secondary legal materials in the form of academic literature and official documents. The results of the study show that the applicable regulations in Indonesia have not provided adequate legal certainty and accountability mechanisms for AI-based cybercrimes. Instead, the EU implements a more structured and risk-based regulatory model. This study concludes that Indonesia needs to reformulate the regulation of cybercrime by explicitly integrating the risks of using AI, harmonizing laws and regulations, and strengthening institutional capacity to realize effective law enforcement in the digital era.